Pengaruh Pengetahuan Ibu dan Peran Petugas Kesehatan Terhadap Pemanfaatan Buku KIA Di Puskesmas Rawat Inap Muara Sabak Timur Kabupaten Tanjung Jabung Timur - Andi Agustina (Universitas Batanghari Jambi, 2023)
The Maternal and Child Health Book (KIA) is a notebook owned by parents and health service providers that is used to monitor maternal health during pregnancy, assess the growth and development of children. The use of the MCH handbook can be optimal if health workers and cadres ensure that the mother and family understand the contents of the MCH handbook, increasing knowledge of the MCH handbook can be done in various ways, one of which is by providing counseling according to the needs of pregnant women.The research design used was a one group pretest-posttest design. It was carried out at the East Muara Sabak Inpatient Health Center in December 2022. The total population was as many as 30 respondents with a sample. Data analysis used the Wilcoxon test.The results showed that the mother's knowledge was quite good (40.0%) became good (76.7%) after attending counseling and the role of health workers was not good (66.7%) increased to good (100%) after attending counseling about the use of MCH book. There is an effect of mother's knowledge on the utilization of the MCH handbook. <0.05).The conclusion obtained in this study is the influence of mother's knowledge and the role of health workers on the use of the MCH handbook at the East Muara Sabak Inpatient Health Center, East Tanjung Jabung Regency. And it is suggested that socialization and ongoing counseling be carried out so that it is hoped that this research can be used as a reference for planning maternal and child health programs.